Perancangan Online Personality Test untuk Mengukur Kepribadian Calon Mahasiswa Universitas Pembangunan Jaya - Muthiah, Syifa Alya; Yulianto, Aries (Esa Unggul University, 2021)
AbstractMistakes in choosing a course of study can make students decide to change study programs or even move universities. This mistake happened at Universitas Pembangunan Jaya (UPJ) where there were 13 students moved study programs from 2017-2019, where 85% of the reason was because the study program that had been taken was not his own desire and was not in accordance with students. The choice of study program is influenced by many factors, one of which is personality. Based on the big five personality theory, there are 5 personality dimensions, namely Openness to experience, Conscientiousness, Extraversion, Agreeableness, and Neuroticism (OCEAN). This study aims to compile an online test to measure the personality of prospective UPJ students whose results can provide recommendations for suitable UPJ study programs. Researchers also conducted a preliminary psychometric test study of this personality test. This online administration makes use of a Google Form linked to a Google Sheet to create a scoring system and interpretation of results. This personality test consists of 50 Likert scale formatted statements, where each dimension is measured by 5 statements, from